Linguistic and cultural skills for communication in global workplaces of the 21st century - Briguglio, Carmela (IGI Global, 2012)
This chapter examines issues in intercultural communication in regard to the use of English as a global language in the workplace of the 21st century. The findings that emerged from data gathered in two multinational companies inform discussion about the sort of communication skills that workers will require in the global workplace. A case study with an Australian undergraduate class served to examine whether the skills identified in multinational workplaces are, in fact, being developed in graduates. Based on all the above, the author has developed a four dimensional model comprising the intercultural communication skills that future graduates, including engineers and IT professionals, will require for global workplaces. Some strategies that will facilitate the development of such skills are also discussed.